1986
DOI: 10.1159/000461513
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Platelet Factor 3 in Platelet Concentrates Stored for Transfusion

Abstract: The amount of platelet factor 3 (PF3) activity expressed in stored platelet concentrates (PC) was measured in conjunction with extracellular LDH levels. Standard manual techniques for preparation of PC resulted in PF3 and LDH levels remarkably higher than those observed in PC prepared by apheresis or special manual plateletpheresis. During storage of PC, PF3 activity rose 2- to 10-fold, while LDH levels rose < 2-fold over starting values. Loss of LDH and appearance of PF3 expressed as a percent of total per pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
1
19
1
Order By: Relevance
“…In the light of evidence of thrombin activity, plasmin activity, and the limited activation of the complement sys tem in the plasma of standard platelet concentrates during storage [12][13][14], the protease inhibitors Thromstop and aprotinin were added along with PGE! and theophylline in the present study of the artificial medium in case plasma carryover was significant.…”
Section: Addition Of Protease Inhibitorsmentioning
confidence: 99%
“…In the light of evidence of thrombin activity, plasmin activity, and the limited activation of the complement sys tem in the plasma of standard platelet concentrates during storage [12][13][14], the protease inhibitors Thromstop and aprotinin were added along with PGE! and theophylline in the present study of the artificial medium in case plasma carryover was significant.…”
Section: Addition Of Protease Inhibitorsmentioning
confidence: 99%
“…This is in agreement with results of Prodouz [ 161 who described intracellular calcium-dependant calpain protease during platelet aging. Extracellular proteolysis of GPIb was also described [17] without inhibition by the addition of any known protease inhibitors in the storage medium [18].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of platelet integrity during storage is closely correlated with an intracellular decrease in cAMP [24]. Prostaglandin-El-induced conversion of ATP to cAMP did not increase in vitro platelet viability, contrary to what occurs when theophyllin inhibits the degradation of CAMP into AMP [18]. A decrease in ATP during storage due to exhaustion of the energetic substrates or to a change from aerobic to anaerobic catabolism was probably responsible for the intracellular CAMP decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin generation has been observed during blood collection [13] and could be responsible for, and supported by, the expression of plate let factor 3 activity by activated platelets [3,14,15], Activation of platelets through the binding of thrombin to the 40-kilodalton platelet protein is a slow process at 21 °C and takes about 5 min to reach steady state [16]. In addition we have found that in PC prepared from blood collected into CPD-adenine, the aggregation response to low doses of collagen is lowered relative to that in PC from blood collected simply into CPD [Solberg MS, in prepa ration], Platelet aggregation and release are inhibited by cAMP [16] and exposure of platelets to physical stimuli such as centrifugation has been reported to diminish cAMP levels [17], Furthermore, during the first centrifu gation the platelets are centrifuged together with the red cells at a ratio of 1:20.…”
Section: Platelet Countmentioning
confidence: 99%